The Effectiveness of Giving Binahong (Anredera cordifolia) Leaf Extract on Granulation Tissue Thickness in Healing White Rat (Rattus novergicus) Cut Wounds - Damayanti, Putri Raina; William, Andy; Wijaya, Gary (International Journal of Public Health Excellence (IJPHE), 2024)
Wounds result in loss of epithelial continuity with or without loss of underlying connective tissue. The dynamic and complex wound-healing process restores tissue integrity and balance. Medicinal plants in herbal medicine, namely Binahong, help heal wounds. This study tested binahong (Anredera cardifolia) leaf extract ointment on the thickness of granulation tissue in white rat (Rattus novergicus) incision wounds. Binahong leaf extract was applied at 15%, 25%, and 35%, then the wound was examined macroscopically and histopathologically. The type of research was a true experiment with a sample of 24 male Wistar rats, six per group, in four groups (control, treatment 1, treatment 2, treatment 3). The histopathological image of granulation tissue thickness shows that the P0 group (blue) has less collagen density. Treatment group 3 (P3) with 35% binahong leaf extract showed thick collagen. Analysis of the Shapiro-Wilk normality test and significant paired t-test values greater than p>0.05 for all groups. The Shapiro-Wilk normality test shows that the data is regularly distributed. Paired T-test showed significant differences in incision wound healing between groups (p-value <0.05). The research concludes that binahong leaf extract has antiseptic, antibacterial, and ascorbic acid properties and protects against oxidation, so it is helpful for wound healing.